Implementation of Multicultural Education at SMP Labschool Jakarta - Farid, Ahmad; Supadi; Santosa, Heru (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2024)
Abstract SMP Labschool Jakarta in the 2023-2024 school year has a total of 684 students from various races, ethnicities, cultures, and religions. Life at SMP Labschool Jakarta is colored by the diversity of students who come from various ethnic, cultural, and regional backgrounds such as Javanese, Sundanese, Betawi, and Batak. In addition, there are various religious backgrounds embraced by students, including Hinduism, Christianity, Catholicism, and the majority of Muslims. This diversity requires serious efforts for educators to maintain harmony in differences and show the spirit of Bhinneka Tunggal Ika. Multicultural education is essential to reduce conflicts arising from these differences and form a character that is open to differences. This study uses a qualitative descriptive method to explore the application of multicultural education in SMP Labschool Jakarta. Data was collected through in-depth interviews, observations, and document analysis. The results of the study show that SMP Labschool Jakarta shows its commitment to multicultural education by designing an inclusive curriculum that is oriented towards national values and justice. This approach is expected to create an inclusive environment and respect diversity, so that multicultural education becomes an integral part of the teaching and learning process in school life.